Antibody drug conjugates: the future of chemotherapy?. Issue 5 (September 2016) - Borcoman, Edith; Le Tourneau, Christophe
Abstract : Purpose of review: The current review describes the rationale and current clinical development of antibody drug conjugates (ADCs), along with their perspectives for the future. Recent findings: Trastuzumab emtansine was the first ADC approved by the U.S. Food and Drug Administration for the treatment of human epidermal growth factor receptor 2 positive metastatic breast cancer in the second-line setting, with a high efficacy and a favorable safety profile. ADC represents an exciting new class of cancer therapeutics that combines a targeted approach for delivering cytotoxic agents. About 30 new ADCs are currently under investigation in oncology. Summary: ADCs are empowered antibodies designed to exploit the targeting ability of monoclonal antibodies (mAbs) by linking them to cytotoxic agents, giving them higher tumor selectivity, and potentially an increased therapeutic window, as compared with cytotoxic agents alone. The key components of ADCs include a mAb, a stable linker and a cytotoxic agent. In linking mAbs with cytotoxic agents, the aim is to optimize the properties of both components, bringing their complementary features together. Trastuzumab emtansine has been the first ADC to be marketed in human epidermal growth factor receptor 2 positive metastatic breast cancer. Current clinical development of ADCs includes a variety of targets, as well as combinations with other therapeutic agents, such as chemotherapy, radiotherapy, targeted therapies, and immune checkpoint inhibitors.